Kajian Filologi dan Hakikat Ilmu Rasa dalam Naskah Raos Jawi - Nur’aini*, Mutiara Suci; Ekowati, Venny Indria; Hartanto, Doni Dwi (Universitas Suryakanca, 2024)
This article will examine ancient texts or manuscripts through philological studies. The research uses library research combined with descriptive research methods and modern philological methods. The objects of the research are Raos Jawi manuscripts and texts. Data collection techniques are through manuscript inventory, manuscript description, text transliteration, text editing, and text translation. Data analysis uses descriptive analysis techniques. In the research, 2 copies of the Raos Jawi manuscript were found. The research only examined 1 Raos Jawi manuscript, manuscript code NB 1582. The results of this research are in the form of a description of the Raos Jawi manuscript and text, transliteration and editing, translation, and the nature of the science of feeling in the Raos Jawi text as follows: (1) The existence of God, (2) true soul, (3) true teacher, (4) paraning dumadi as the origin of humans, (5) humans as thinking and creative beings, (6) humans as socially feeling beings.Keywords: philology; science of taste; Raos Jawi script Abstrak: Artikel ini akan menelaah teks atau naskah kuno melalui kajian filologi. Penelitian menggunakan jenis penelitian pustaka (library research) yang dipadukan dengan metode penelitian deskriptif serta metode filologi modern. Objek penelitian yaitu naskah dan teks Raos Jawi. Teknik pengumpulan data melalui inventarisasi naskah, deskripsi naskah, transliterasi teks, penyuntingan teks, dan penerjemahan teks. Analisis data menggunakan teknik analisis deskriptif. Dalam penelitian ditemukan 2 eksemplar naskah Raos Jawi. Penelitian hanya meneliti 1 naskah Raos Jawi, kode naskah NB 1582. Hasil penelitian ini berupa deskripsi naskah dan teks Raos Jawi, transliterasi dan suntingan, terjemahan, serta hakikat ilmu rasa dalam teks Raos Jawi sebagai berikut: (1) Keberadaan Tuhan, (2) sukma sejati, (3) guru sejati, (4) paraning dumadi sebagai asal mula manusia, (5) manusia sebagai makhluk berpikir dan mencipta, (6) manusia sebagai makhluk berperasaan sosial.Katakunci: filologi; ilmu rasa; naskah Raos Jawi